OASISMENCLOTHES ARE UNIQUEAPPEARANCES - Gaffarova Nurkhan Absokhat kizi (European Science Publishing, 2024)
In this article, the appearance, types, and their important aspects and uniqueness of men's clothing, formed in the Surkhan oasis and developed since ancient times, are explained with brief examples. Also, the dress style and special aspects of the men of the ancient oasis have been touched upon a little.
Keywords: Oasis Men's Clothing